China - Meeting the Challenges of Offshore and Large-Scale Wind Power : Strategic Guidance - World Bank (World Bank, 2012)
In view of the escalating global problems associated with the environment, energy, and natural resources, especially the increasing sign of global climate change, wind power is receiving more and more high-level attention on a global scale, and it has reached a rapid rate of development as a result of the combined efforts of various countries. The world's installed capacity of wind power has already surpassed 100 GW, and wind power has become an essential part of the world's energy structure. This publication comprises three main parts: i) part A contains the key messages emerging from the research and analytical work undertaken by Garrad Hassan and Partners Limited, the team of Chinese experts led by the national energy administration, and staff and consultants of the World Bank; ii) part B comprises the Garrad Hassan and Partners Limited study, 'implementation guidance for offshore and large-scale onshore wind power development in China,' and its annexes; and iii) part C focuses on the workshop on offshore and intertidal wind power development in China, which was held in Beijing in January 2009, and it includes technical notes on three main issues discussed during the workshop, remarks by senior officials from the Government of China, and the presentation by the World Bank during the event.